THE USE OF CODE SWITCHING IN ENGLISH TEACHING LEARNING PROCESS IN JUNIOR HIGH SCHOOL - ATMA JONAR ASIH; RIDWAN SYAHPUTRA; ULPAH MAISARI (JURNAL ILMIAH SIMANTEK, 2021)
This study concerns investigates the value of the use of code switching in English teaching learning process in junior highschool. Student and a teacher in SMP INTI NUSANTARA Tebing Tinggi involve as the subjects of this study. The purpose ofthis research is to investigate the value of lesson study in used code switching by the teacher. This case study obtaine thedata by ways of observations among students and teacher in class. This research aim to analyze the types of code switchingused by the teacher and the students. The reserach methodology uses qualitative. Qualitative research involves collectingdata from observation. The function of this research is how far is the useful of code switching in teaching learning in class.Generally this study has a treatment which came up from the teaching learning process in class.